RAS Family GTPases - Der, Channing (Proteins and Cell Regulation, 2006)
Since 1982, Ras proteins have been the subject of intense research investigation by the biomedical research community. The wide interest in Ras has been stimulated for three key reasons. First, their frequent mutational activation in human cancers establishes Ras proteins as important mediators of oncogenesis and targets for anti-cancer drug discovery. Second, Ras proteins act as signalling nodes activated by diverse extracellular stimuli, and activated Ras in turn regulates a diversity of cytoplasmic signalling networks. Third, Ras proteins are founding members of a large superfamily of Ras-related small GTPases. Over 150 Ras-related small GTPases are found in the human genome, with orthologs found in all vertebrate species and invertebrates. This book features chapters by leading investigators in the field that highlight the current state-of-the art in Ras biochemistry, structure and biology. This book is an excellent reference for students in the biomedical sciences and for investigators in the field.